Unfair discrimination in prenatal aneuploidy screening using cell-free DNA?. (March 2016) - Rolfes, Vasilija; Schmitz, Dagmar
Abstract: Non-invasive prenatal testing on the basis of cell-free DNA of placental origin (NIPT) changed the landscape of prenatal care and is seen as superior to all other up to now implemented prenatal screening procedures – at least in the high-risk population. NIPT has spread almost worldwide commercially, but only in a few countries the costs of NIPT are covered by insurance companies. Such financial barriers in prenatal testing can lead to significant restrictions to the average range of opportunities of pregnant women and couples, which on an intersubjective level can be defined as unfair discrimination and on an individual level weakens reproductive autonomy. Given that enabling reproductive autonomy is the main ethical justification for offering prenatal (genetic) testing, these barriers are not only an issue of justice in health care, but are potentially counteracting the primary purpose of these testing procedures.